2021
DOI: 10.3389/fimmu.2021.678156
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sex Differences on Mortality in Patients With Sepsis After Trauma: A Nationwide Cohort Study

Abstract: ObjectiveSepsis is the leading cause of death in intensive care units, and sepsis after trauma is associated with increased mortality rates. However, the characteristics of sepsis after trauma remain unknown, and the influence of sex on mortality remains controversial. This study aimed to assess the role of sex in in-hospital mortality in patients with sepsis after trauma.MethodsWe performed a retrospective cohort study involving several emergency hospitals (n=288) in Japan. The data of patients with trauma wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 38 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…Sex also has an impact on the prognosis of trauma patients; the risk of in-hospital death in men is 2.08 times higher than that in females. Many studies have confirmed that acknowledging possible gender differences in a wider range of trauma symptoms may have clinical benefits (17,18). It is very important to select an easily detected and available laboratory index to further predict the prognosis of patients or improve the accuracy of prognosis prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Sex also has an impact on the prognosis of trauma patients; the risk of in-hospital death in men is 2.08 times higher than that in females. Many studies have confirmed that acknowledging possible gender differences in a wider range of trauma symptoms may have clinical benefits (17,18). It is very important to select an easily detected and available laboratory index to further predict the prognosis of patients or improve the accuracy of prognosis prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual dimorphism in response to bacterial infections has been extensively described in hospital environments, where it has been observed that men were more susceptible to bacteremia than women (Bösch et al, 2018 ; McGowan Jr. et al, 1975 ) and mortality was less common in women after a septic infection than men (Kondo et al, 2021 ). In the context of central nervous system (CNS), numerous neurological and psychiatric disorders show sex differences in incidence, age of onset, symptomatology or outcome and most of these disorders course with neuroinflammation (Giatti et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A predictive score has been developed to predict sepsis risk among trauma patients [ 10 ]. A nationwide cohort study reported a relationship between sex differences and mortality in patients with sepsis after trauma [ 11 ]. In summary, recent research has predominantly focused on the risk factors for post-traumatic sepsis, and few studies have examined risk factors associated with the in-hospital mortality of trauma patients with sepsis.…”
Section: Introductionmentioning
confidence: 99%